The Epigraphy and History of Boeotia : New Finds, New Prospects - Papazarkadas, Nikolaos (Brill Studies in Greek and Roman Epigraphy Ser, 2014)
Contents -- Preface -- Abbreviations -- List of Contributors -- Introduction (Papazarkadas) -- Section I. Boeotian History: New Interpretations -- Ethnic Identity and Integration in Boeotia: The Evidence of the Inscriptions (6th and 5th Centuries BC) (Beck) -- Creating a Common Polity in Boeotia (Mackil) -- ΕΧΘΟΝΔΕ ΤΑΣ ΒΟΙΩΤΙΑΣ. The Expansion of the Boeotian Koinon towards Central Euboia in the Early Third Century BC (Knoepfler) -- Between Macedon, Achaea and Boeotia: The Epigraphy of Hellenistic Megara Revisited (Robu) -- A Koinon after 146? Reflections on the Political and Institutional Situation of Boeotia in the Late Hellenistic Period (Müller) -- Section II. The New Epigraphy of Thebes -- The Inscriptions from the Sanctuary of Herakles at Thebes: An Overview (Aravantinos) -- Four Inscribed Bronze Tablets from Thebes: Preliminary Notes (Matthaiou) -- Two New Epigrams from Thebes (Papazarkadas) -- New Inscribed Funerary Monuments from Thebes (Bonanno Aravantinos) -- Section III. Boeotian Epigraphy: Beyond Thebes -- Tlepolemos in Boeotia (Schachter) -- Digging in Storerooms for Inscriptions: An Unpublished Casualty List from Plataia in the Museum of Thebes and the Memory of War in Boeotia (Kalliontzis) -- Just as It Has Been Written: Inscribing Building Contracts at Lebadeia (Pitt) -- Manumission in Hellenistic Boeotia: New Considerations on the Chronology of the Inscriptions (Grenet) -- Land Administration and Property Law in the Proconsular Edict from Thisbe (Syll. 3 884) (Pernin) -- Index Locorum -- General Index -- Greek Names and Terms.